Planowanie i kształtowanie stanu zatrudnienia: Planning and creating of employment - Rucińska, Patrycja; Kołodziejczyk, Agnieszka (Management and Administration Journal, 2021)
There is no company which could exist without people. Those employed by a company are to create an organization. Hence, gaining adequate staff is a condition of effectivefunctioning of the company. The aim of this article is to approach the essence of workforceplanning, recruitment and selection of candidates.